PENGARUH MULTIDIMENSIONAL FAMILY THERAPY TERHADAP KETERGANTUNGAN NARKOBA PADA REMAJA: SYSTEMATIC REVIEW - Widiya Sari, Ilma; Sutanta (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2019)
Drug abuse are complex problems in adolescents because it can cause physical, psychological and social problems. Rehabilitation efforts are needed to reduce drug abuse in adolescents, one of this is multidimensional family therapy (MDFT). MDFT emphasizes the context of adolescent development and family function. The purpose of this study was to determine the effect of MDFT on drug abuse in adolescents. This research is a systematic review to synthesize research articles by adjusting the inclusion and exclusion criteria. Articles that include the inclusion and exclusion criteria are analyzed the quality of these studies with the Critical Assessment Capability Program for RCT. The results of the research article are read by compiling the extraction data, then the data is synthesized for discussion. The results of a review of four research articles show that MDFT reduce drug abuse in adolescents. The results of these studies can be used as evidence based on nursing practice and nursing research. MDFT can be adopted as an intervention in the treatment of adolescents with drug abuse. Further research is needed to find out the effect that might occur and moderator variables that can affect the effectiveness of MDFT.